Needle Decompression Causing Pericardial and Pulmonary Artery Injuries in Patients With Blunt Trauma: Two Case Reports and Literature Review - Husham Abdelrahman MD; Sajid Atique MD; Ahmad G. Kloub MD; Suhail Y. Hakim MD; James Laughton MD; Yassir S. Abdulrahman MD; Ayman El-Menyar MD; Hassan Al-Thani MD (SAGE Publishing, 2023)
Tension pneumothorax (TPX) is a severe chest complication of blunt or penetrating trauma. Immediate decompression is the lifesaving action in patients with TPX. Needle decompression (ND) is frequently used for this purpose, particularly in limited resources setting such as the prehospital arena. Despite the safe profile, the blind nature of the procedure can result in a serious range of complications, including injury to the vital intrathoracic structures such as the lungs, great vessels, and heart. Here, we reported 2 cases of blunt chest trauma resulting in TPX demanding immediate ND; however, nonintentional pericardial and pulmonary artery injuries occurred. The first case was a 42-year-old man with a needle-related pulmonary artery injury that required surgery. The second case was a 19-year-old man in whom a needle-related pneumopericardium occurred and was treated conservatively. In both cases, trained personnel performed the ND. Although ND in the field is a lifesaving intervention, it may further complicate the patient condition. Therefore, it should be performed in adherence to the universal guidelines.